(ab - 5a + 6b -30)^4 (a^2 + 6a +9)^2 ((аb-5a)+(6b-30))^4 (a^2 + 6a +9)^2
* = * =
(ab + 6a +3b +18)^4 (10b - b^2 - 25)^2 ((ab+6a)+(3b+18))^4 (10b - b^2 - 25)^2
(a(b-5)+6(b-5))^4 (a+3)^4 (a+6)^4(b-5)^4 (a+3)^4 (a+6)^4
(a(b+6)+3(b+6))^4 (b-5)^4 (a+3)^4(b+6)^4 (b-5)^4 (b+6)^4
(ab - 5a + 6b -30)^4 (a^2 + 6a +9)^2 ((аb-5a)+(6b-30))^4 (a^2 + 6a +9)^2
* = * =
(ab + 6a +3b +18)^4 (10b - b^2 - 25)^2 ((ab+6a)+(3b+18))^4 (10b - b^2 - 25)^2
(a(b-5)+6(b-5))^4 (a+3)^4 (a+6)^4(b-5)^4 (a+3)^4 (a+6)^4
* = * =
(a(b+6)+3(b+6))^4 (b-5)^4 (a+3)^4(b+6)^4 (b-5)^4 (b+6)^4